Spatial analysis of Traffic accidents in Baghdad governorate using geographic information systems - Ali, Bashar Jebur (Al-Adab Journal, 2022)
The research aims to analyze the reality of traffic accidents in the province of Baghdad, through the distribution of the number of traffic accidents over the districts of the province of Baghdad, and the total for the year (2020) (871) accidents, and there are multiple factors that contributed to the rise in traffic accidents, including the nature of the traffic accident (coup, run over, collision), as the collision accidents ranked first with (39.7%) accidents, and the road category contributed as an influencing factor in traffic accidents. The largest percentage of (51.5%) accidents, while the traffic accidents factor according to their type and severity, the accidents accompanying the injured only constituted the highest percentage of (587) accidents. Because of the import of cars without controls that specify the conditions of durability and safety, and the traffic accident factor, according to the causes of the accident, whose causes are attributed to the driver in the first place, amounted to (611) accidents, due to driving vehicles without a driving license. In particular, run-over accidents amounted to (417) accidents and (81) accidents for males and females, while the traffic accidents factor ranked according to the main causes of their occurrence on a high percentage, represented by high speed in the first ranks with a total of (585) accidents, and traffic accidents focused on the District level, according to a factor, as a result of accidents in the Rusafa and Karkh districts in the first and second place, respectively, by (242) accidents, (154) accidents, and cars topped the type of traffic accident salon according to the vehicle type factor, by (480) accidents, and the standard degree of traffic accidents at the level of districts was higher The ratio in the districts of Rusafa and Karkh, respectively, by (2.4) accidents and (1.2) accidents, and the ratios of the number of traffic accidents to the number of deaths were (0.3) (accident / death), while the results of the ratio of injuries to the number of accidents were (0.8) (accident / injury). Finally, the percentages of the number of deaths for every (10) injuries came at a rate of (0.3) (dead/ injured (